1999
DOI: 10.1101/gad.13.14.1834
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of Fgf8 causes failure of cell migration in the gastrulating mouse embryo

Abstract: Fgf8 and Fgf4 encode FGF family members that are coexpressed in the primitive streak of the gastrulating mouse embryo. We have analyzed the phenotype of Fgf8 −/− embryos and discovered that they fail to express Fgf4 in the streak. In the absence of both FGF8 and FGF4, epiblast cells move into the streak and undergo an epithelial-to-mesenchymal transition, but most cells then fail to move away from the streak. As a consequence, no embryonic mesoderm-or endoderm-derived tissues develop, although extraembryonic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
431
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(461 citation statements)
references
References 72 publications
27
431
1
2
Order By: Relevance
“…In the zebrafish, this placode cavi- fgf8 (Reifers et al, 1998) Growth factor Small ear, abnormal neurogenesis (Adamska et al, 2000;Phillips et al, 2001) Targeted disruption (Sun et al, 1999) colourless (cls) sox10 (Dutton et al, 2001b) HMG box transcription factor…”
Section: Introduction To Zebrafish Ear Anatomymentioning
confidence: 99%
“…In the zebrafish, this placode cavi- fgf8 (Reifers et al, 1998) Growth factor Small ear, abnormal neurogenesis (Adamska et al, 2000;Phillips et al, 2001) Targeted disruption (Sun et al, 1999) colourless (cls) sox10 (Dutton et al, 2001b) HMG box transcription factor…”
Section: Introduction To Zebrafish Ear Anatomymentioning
confidence: 99%
“…3E). Besides ␣-actin, expression of other mesodermal markers, such as derriere (Sun et al, 1999a), brachyury (Cunliffe and Smith, 1992), and myoD (Hopwood et al, 1989), was elevated in the Neptune-injected caps (data not shown). Thus, it was shown that Neptune has an activity to induce mesoderm directly from animal cap cells even though Neptune is a DNAbinding protein and a factor related to erythropoietic differentiation (Kawahara and Dawid, 2000;Huber et al, 2001).…”
Section: Mesoderm-inducing Activity Of Neptune In Animal Cap Explantsmentioning
confidence: 93%
“…Since previous studies showed that FGF-related factors such as brachyury and derriere, have similar posterior-inducing activity (Cunliffe and Smith, 1992;Conlon et al, 1996;Sun et al, 1999a), we further investigated the relationship of these factors. Double staining of neptune and brachyury mRNA in gastrulating embryos indicated that these two transcripts are expressed closely to each other (data not shown).…”
Section: Activity Of Neptune For Formation Of Posterior Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF8 was originally isolated from the conditioned medium of an androgen dependent mouse mammary carcinoma line (SC-3) as an androgen induced growth factor (AIGF) and was later assigned as a member of the fibroblast growth factor family on the basis of structural similarity (Tanaka et al, 1992). FGF8 appears to have an important role in embryogenesis and is expressed in several areas of the developing mouse and may play a critical role in gastrulation and the development of the face, limb and central nervous system (Vogel et al, 1996;Neubuser et al, 1997;Meyers et al, 1998;Ye et al, 1998;Tucker et al, 1999;Sun et al, 1999). Little expression of FGF8 has been found in adult mouse tissues with comparatively low amounts detected only in the ovaries and testes (MacArthur et al, 1995a;Lorenzi et al, 1995).…”
mentioning
confidence: 99%